Integrating the Principles of Prophet Ibrahim's Exemplary Leadership in Human Resource Management within Islamic Educational Institutions: A Literature Review - Ari Hikmawati; Imam Makruf; Islah Gusmian; Agus Wedi (STAI Hubbulwathan Duri, 2024)
This study explores the integration of Prophet Ibrahim's leadership principles into Human Resource Management (HRM) practices within Islamic educational institutions. Prophet Ibrahim is revered for his ethical values and exemplary leadership, which offer insights into developing HRM strategies that align with Islamic values and global HRM standards. A literature review methodology was adopted, drawing on existing academic sources and supporting literature to identify and analyze the leadership principles of Prophet Ibrahim and their relevance to HRM. The findings indicate that Prophet Ibrahim’s leadership principles—such as integrity, justice, obedience, and discipline—provide a strong ethical foundation for HRM practices. These values contribute to fostering an inclusive, fair, and effective organizational culture in Islamic educational institutions. Integrating Prophet Ibrahim’s leadership values into HRM practices ensures alignment with Islamic values while enhancing governance standards. This approach promotes ethical decision-making, equitable management, and discipline, resulting in a holistic HRM framework that balances religious and global benchmarks. The study underscores the relevance of Prophet Ibrahim's leadership principles in shaping HRM practices in Islamic educational institutions. By embedding these principles, institutions can cultivate a values-driven culture that meets both religious and professional standards. Future research should explore practical implementation strategies to enhance HRM effectiveness further.